Synthesis of SnPS3 nanosheets for anode in lithium ion battery application - Wirahara, Jonathan Kenichi (2019)
The SnPS3 is a future candidate as an anode in lithium ion batteries (LIB). In this 21st century, the demands for highly efficient energy storage are increasing every year as technologies constantly undergoes evolution. For example, there are many researches which focus on how to produce efficient and high-density energy storage for electric cars. By investigating and analysing SnPS3 electrochemical properties, there is a possibility produce higher density battery. The present lithium ion batteries only deliver a capacity of 372 mAh g-1 and less than adequate energy density. There are many interests in researching different type of materials for anode in LIB. One of the materials which has been thoroughly researched are the metal phosphorus trichalcogenides groups and these materials have been shown to be one of the potential materials to be an anode inside LIB. The SnPS3 is one of the promising materials from metal phosphorus trichalcogenides that is used as an electrode in lithium ion batteries. The bulk SnPS3 (BSPS) is synthesized via chemical vapour mass transport and the BSPS is then exfoliated to form exfoliated SnPS3 (ESPS) with polycrystalline structure. The ESPS rate capability also shows remarkable performance where the capacity is 1025.2 and 245.9 mAh g-1 whereas the BSPS capacity is only 324.8 and 19.4 mAh g-1 with both at a rate of 0.1 and 5 A g-1 respectively. Furthermore, the exfoliated crystals show even better performance than its bulk counterpart where ESPS capacity reaches 603.1 mAh g-1 even after 100 cycles while BSPS capacity only reaches 28.1 mAh g-1 with both at the current density of 1 A g-1.